PEMAHAMAN HUKUM DAN PENANAMAN PENDIDIKAN KARAKTER DALAM PENCEGAHAN TINDAKAN PERUNDUNGAN ATAU BULLYING PADA SISWA DI SMA WIDYA DARMA SURABAYA - Resi Apriani Hergita Candra; Yuniarto Wiryo Nugroho; Dwi Riwayat Susiana; M Ubaidillah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Bullying is an act of intimidating and forcing a weaker individual or group to do something againts their will the intention of causing physical, mental or emotional harm through verbal or physical harassment and assault. In the 1945 State Constitution Article 28 B Paragraph 2, which states “Every child has the right to survival, growth and development and the right to protection from violence and discrimination”. This means that every Indonesian child has the right to live, grow in an environment that is conducive physically, mentally abd develop without interference in the form of violence. This article strictly speaking, children must not receive discrimination in any form.The impact and benefits of socialization activities on legal understanding and character education are that students gain additional knowledge about preventing bullying against themselves and their environment and gain in depth insight into the impact of bullying among teenagers, so that students are able to apply ways to deal with it when bullying accurs at scholl and prevent bullying at school.